1999
DOI: 10.1080/07328319908044853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Carbocyclic Ribonucleotides

Abstract: The carbocyclic analogs of CMP, UMP, GMP, IMP, and ribo-TMP, of the same absolute configuration as the naturally occurring beta-D-ribofuranose-based ribonucleoside monophosphates, have been synthesized. The synthetic route employed Mitsunobu coupling of the heterocycles, appropriately protected where necessary, with a differentially protected, chiral carbocyclic core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the cytosine series we found that the normal N 4 -benzoyl or N 4 -acetyl protected cytosine did not give satisfactory yields under the Mitsunobu conditions. The best yields were achieved with N 4 -isobutyrylcytosine as the nucleophile [1921]. In the guanine series, the N 2 -isobutyryl, O 6 -diphenylcarbamoyl protected guanine worked well (Scheme 3) [22].…”
Section: Resultsmentioning
confidence: 99%
“…In the cytosine series we found that the normal N 4 -benzoyl or N 4 -acetyl protected cytosine did not give satisfactory yields under the Mitsunobu conditions. The best yields were achieved with N 4 -isobutyrylcytosine as the nucleophile [1921]. In the guanine series, the N 2 -isobutyryl, O 6 -diphenylcarbamoyl protected guanine worked well (Scheme 3) [22].…”
Section: Resultsmentioning
confidence: 99%